2017
DOI: 10.1017/mor.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development of the Intellectual Property Rights System in China and Challenges Ahead

Abstract: As Peng, Ahlstrom, Carraher, and Shi (2017) rightly noted, Intellectual Property Rights (IPR) protection in a country is not static. It evolves over time. Peng et al. (this issue) revealed through their historical analysis that during the 19th century, the US was not a leading IPR advocate but a leading IPR violator. It was only when indigenous inventors, authors, and organizations of the US emerged and demanded protection of their IPR in foreign countries in the late 19th century that the US passed the Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 8 publications
(9 reference statements)
0
24
0
Order By: Relevance
“…Therefore, a notable trend in the field of the latest management technologies is establishment of an organizational culture as an environment where a unique amalgamation of norms, values and behavioral models defines the way of uniting employees for achievement of strategic goals of the company. At the same time, understanding of variability of organizational culture impact at different levels of analysis becomes a crucial firm-level factor, enabling the company to take a stand and form new business model innovations [19], transforming knowledge, ideas, technologies and resources into economic values, and linking ideas and technologies to their economic results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a notable trend in the field of the latest management technologies is establishment of an organizational culture as an environment where a unique amalgamation of norms, values and behavioral models defines the way of uniting employees for achievement of strategic goals of the company. At the same time, understanding of variability of organizational culture impact at different levels of analysis becomes a crucial firm-level factor, enabling the company to take a stand and form new business model innovations [19], transforming knowledge, ideas, technologies and resources into economic values, and linking ideas and technologies to their economic results.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the distribution of patent value is extremely unbalanced because many patents have a low value and compartively few patents have high value (Harhoff, Narin, Scherer & Vopel, 1999; Schankerman & Pakes, 1986). In addition, many patent applications by enterprises are strategic, political, and symbolic, which means the purpose of applying for patents is to obtain subsidies or other resources, rather than carry out real innovation activities to meet the actual market demand or technological development needs (Huang, 2017; Jiang, He & Lu, 2019; Li, 2012; Li & Zheng, 2016).…”
Section: Framework and Measurementmentioning
confidence: 99%
“…The results can be explained using explicit indicators and duration. In terms of explicit indicators, these indicators of patent quantity are clearly required in policy texts, so firms must achieve such requirements to guarantee projects, as previous studies have shown (Huang, 2017; Jiang et al, 2019; Li & Zheng, 2016). With regard to duration, the “top‐down” projects usually last for a longer period, generally 2–3 years, while the “bottom‐up” projects last for a relatively shorter period, generally 1–2 years, and the time frame for the latter often includes one year before the project is granted.…”
Section: Innovation Policy Performancementioning
confidence: 99%
“…First, while China keeps imitating the West to develop its domestic institutions such as a proper intellectual property rights (IPR) regime, the Chinese entrepreneurs may have created a unique way of addressing problems associated with a formal institutional void (Puffer et al , 2010). It is argued that China is on the way to voluntarily improve its IPR protection as it sees the needs to protect home-made IPR (Cheng and Huang, 2016; Huang, 2017), just as what the US did when the US transformed itself from an IPR violator to an IPR protector in the late nineteenth-century (Peng et al , 2017a, 2017b).…”
Section: Overview Of Research and Special Issue Articlesmentioning
confidence: 99%